Peningkatan Pemahaman Siswa Dalam Pembelajaran IPA Materi Konsep Listrik Melalui Penggunaan Alat-Alat Listrik Di Kelas VI Sekolah Dasar - Marcelinus Widananta (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study entitled "Improving students' understanding of science learning about the concept of electricity through the use of electrical tools in class VI of SD Negeri Pudakpayung 01, SD Negeri Pudakpayung 02, SD Negeri Pudakpayung 03". The focus of the problem of improvement in this report is (1) students' low understanding of the concept of electricity (2) students pay less attention to learning. (3) Students do not understand the daily test questions so that their scores are low. The objectives to be achieved from this research are (1) To describe the use of electric tools to increase student learning interest about "Presenting information about the transfer and change of electrical energy" in class VI students. (2) To analyze the impact of the use of electric teaching aids in science learning on improving the learning outcomes of class VI students. (3) To analyze the impact of the use of electric tools on science learning in increasing students' interest and attention to learning. This research begins with the teacher's perceived problems in learning. The activity is continued by analyzing and formulating problems, then planning research in the form of corrective actions, observing, and reflecting on the actions taken repeatedly ending until the level of student completeness can be achieved. From the results of the analysis and conclusions obtained from this study are (1) Learning by using concrete media in the form of electrical tools can increase the activity and involvement of grade VI students in learning science as the basic competency "Presenting information about the transfer and change of electrical energy". (2) The use of concrete visual aids in the form of electrical tools can increase students' understanding of class VI in science learning the basic competence "Presenting information about the transfer and change of electrical energy" (3) Through experimental and demonstration methods using electrical tools it turns out to be able to improve learning outcomes of class VI students in science learning basic competency "Presenting information about the transfer and change of electrical energy"